Un nuovo frammento della «Vita s. Iohannis Gualberti» di Gregorio di Passignano (BHL 4400) = An Unknown Fragment Of «Vita S. Iohannis Gualberti» Of Gregorio Of Passignano - Righetti, Jacopo (Hagiographica, 2023)
The purpose of this article is to conduct a study and produce a critical edition of a fragment of the Vita of Gregorio of Passignano (BHL 4400) which appears in two different versions in the manuscript Milano, Biblioteca Ambrosiana, F 117 sup. Following a preliminary section devoted to the palaeographical analysis of the codex, the article examines the relationship between the two versions of the text. This analysis includes a discussion of authorship and the context of writing. The discovery of this fragment, which was not previously known to scholars, provides new insights into the work of Gregorio, the motivations behind it, and the cultural milieu in which it was produced.